2018
DOI: 10.1002/acn3.587
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcranial magnetic stimulation in the treatment of chronic tinnitus

Abstract: ObjectiveRepetitive transcranial magnetic stimulation (rTMS) is currently being tested for suppressing the symptoms of subjective chronic primary tinnitus, although its effect is controversial. The aim of this randomized double‐blinded controlled trial was to determine the effect of rTMS with unique settings for tinnitus treatment.MethodsFifty‐three adult patients suffering from chronic subjective unilateral or bilateral nonpulsatile primary tinnitus for at least 6 months were randomly assigned to rTMS (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 28 publications
1
65
0
1
Order By: Relevance
“…Restrained by the limited number of eligible studies and the nature of the target population, more proposals to encourage large-sample, multi-center, randomized double-blind trials are needed for further veri cation. Left tem cort Formanek M 2018 [5] Czech Republic Folmer RL 2015 [23] The USA [24] Taiwan, China Left prim Noh TS 2019 [25] South Korea 1-Hz-rTMS (2,000 pulses over the AC and 1,000 pulses over the DLPFC, 110% or lower motor threshold )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Restrained by the limited number of eligible studies and the nature of the target population, more proposals to encourage large-sample, multi-center, randomized double-blind trials are needed for further veri cation. Left tem cort Formanek M 2018 [5] Czech Republic Folmer RL 2015 [23] The USA [24] Taiwan, China Left prim Noh TS 2019 [25] South Korea 1-Hz-rTMS (2,000 pulses over the AC and 1,000 pulses over the DLPFC, 110% or lower motor threshold )…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies [5,15,17,19,20,23,27,[27][28][29][30][31]36,39] reporting adverse events after rTMS sessions were meta-analyzed using a xed-effect model, with nonsigni cant heterogeneity among the studies (I 2 = 37%, P = 0.13). The results showed a nonsigni cant difference in the incidence of adverse events between the rTMS and sham-rTMS groups (12.55% vs. 13.38%, OR: 1.11, 95%CI: 0.51-2.42, P = 0.79) (Fig.7).…”
Section: Adverse Eventsmentioning
confidence: 99%
“…18 In a study conducted by Ho Yun Lee revealed that there was reduction of THI score of ~28.69 points following bifrontal transcranial direct current stimulation. 21 Recently new treatment options have emerged in form of repetitive transcranial magnetic stimulation and deep brain stimulation. However, most of them are still under investigation for their effect.…”
Section: Discussionmentioning
confidence: 99%
“…Formanek et al found that there was no significant effect of repetitive transcranial magnetic stimulation on THI. 21 Past research has demonstrated significant reduction in THI by deep brain stimulation, but being an experimental and invasive procedure, its effectiveness is under debate. 22…”
Section: Discussionmentioning
confidence: 99%
“…Extensive means of treating tinnitus have been developed, which include medications ( von Boetticher, 2011 ; Bhatt et al , 2016 ), counselling and cognitive behaviour therapy, transcranial magnetic stimulation ( Kreuzer et al , 2017 ; Formánek et al , 2018 ), transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS) ( Bae et al , 2020 ), tinnitus retraining therapy ( Scherer et al , 2014 ; Kim et al , 2016 ; Lee et al , 2019 ), relaxation therapy, hearing aids ( Searchfield et al , 2010 ) and sound therapy ( Hall et al , 2015 ; Langguth, 2015 ; Blakley, 2016 ; Plein et al , 2016 ; Makar et al , 2017 ). According to the clinical practice guidelines of tinnitus, sound therapy is one of the recommended treatments ( Tunkel et al , 2014 ) and is used as a standard treatment in the UK ( Baguley et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%